2023
DOI: 10.1039/d2ta08303e
|View full text |Cite
|
Sign up to set email alerts
|

Achieving high energy storage in BaTiO3/rGO/PVDF nanocomposites by regulating the charge transfer path at the hetero-interface

Abstract: Superior energy storage performance of PVDF-based nanocomposites such as discharged energy density or efficiency has been reported, leading to a lower volume, lightweight system, or high reliability for film capacitors....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The SEM image of the TiO 2 particle agglomerates is shown in Figure S5, which shows the agglomerates with diameters of about 200 nm. It has been shown that due to the principle of incompatibility at the organic\inorganic interface, the mass accumulation of inorganic fillers causes significant structural defects at the organic/inorganic interface of the hybrid film, resulting in considerably decreased insulation capability, which will eventually reduce the ability of the combined material to store energy. …”
Section: Resultsmentioning
confidence: 99%
“…The SEM image of the TiO 2 particle agglomerates is shown in Figure S5, which shows the agglomerates with diameters of about 200 nm. It has been shown that due to the principle of incompatibility at the organic\inorganic interface, the mass accumulation of inorganic fillers causes significant structural defects at the organic/inorganic interface of the hybrid film, resulting in considerably decreased insulation capability, which will eventually reduce the ability of the combined material to store energy. …”
Section: Resultsmentioning
confidence: 99%
“…[18] Except for the role of boosting 𝛽 phase content of PVDF-TrFE composite film, the presence of GaIn droplets as a conductive filler are also helpful for amplifying the local electric field benefitting the higher polarizability of PVDF-TrFE and corresponding piezoelectricity. [19] As discussed above, the oxidation layer thickness has shown a significant effect on the 𝛽 phase content of PVDF-TrFE composite film. It is generally accepted that Ga 2 O 3 shell layer was naturally oxidized from GaIn core as Ga is easier to be oxidized, thus then the electron density gradient would be generated by the change of its thickness.…”
Section: (Supporting Information)mentioning
confidence: 86%
“…On the one hand, the improved graphitization of the carbon shell could anchor the carriers around its surface to optimize the charge transfer paths. 24 The charge preferentially migrated along the interface region and the carbon shell (Fig. 8a), which inhibited the development of the conductive path in the polymer matrix, resulting in suppressed conductivity loss of the composites.…”
Section: Dielectric Properties Of the Composite Filmsmentioning
confidence: 99%
“…Therefore, hybrid fillers combining the ceramic fillers with the conductive fillers have been studied, [24][25][26][27][28] which are expected to achieve a high dielectric constant and relatively low dielectric loss at a low filling amount. Constructing a core-shell structure is considered an effective strategy among these hybrid fillers.…”
Section: Introductionmentioning
confidence: 99%